The Impact of patriarchy on a woman’s life: A Study on the Life of Nora in Hendrik Ibsen’s A Doll House: The Impact of in Hendri Ibsen’s A Doll’s House Patriarchy on A Woman’s Life: A Study on the Life of Nora - Prasetiani, Siti Fatimah; Wuntu, Ceisy; Lolowang, Imelda (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research is intended to reveal the impact of patriarchy in Hendrik Ibsen’s A Doll’s House. In conducting this research, the researchers use qualitative method. The data are collected in the forms of word, and need the researchers’ active participation and also the deep analysis of the research. The researchers use Marxist feminist that considers describing women’s basic material weakness and women’s statues and class on the family. The researchers also use the three structures of patriarchy by Walby to classify the data. The first result is the impact of patriarchy in economic control. Second result is the impact of patriarchy in culture structure such as woman subordination and gender stereotype, and the third results is the impact of patriarchy in violence such as Violation of Women’s right and Verbal violence.